2022
DOI: 10.1002/aepp.13280
|View full text |Cite
|
Sign up to set email alerts
|

Consumer spending patterns for plant‐based meat alternatives

Abstract: This paper uses Nielsen Homescan data from 2014 to 2019 to investigate consumer spending on plant‐based meat alternative (PBMA) products. First, we measure determinants of different PBMA spending levels and summarize spending on PBMA and other food products. We then examine spending over time on PBMA and other food items when a household first purchases a PBMA product. A household spends USD 8 on PBMA products in the first month it purchases PBMA. PBMA spending, however, drops by over 75% in the months followi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 35 publications
2
5
0
Order By: Relevance
“…Meanwhile, it could also be contributed by those consumers with both vegetarian–flexitarians and meat‐eaters in their household. In line with our results, a recent study utilizing the Nielsen Consumer Panel data (Cuffey et al, 2021) found that the majority of consumers had not consumed PBMA by 2019, and PBMA spending among the users dropped 75% after the initial purchase, indicating most consumers were probably experimenting with PBMA instead of consuming it regularly. Utilizing national survey data, Taylor et al (2023) also found that consumers do not consume beef and PBMA entirely exclusively of each other.…”
Section: Discussion and Conclusion Remarkssupporting
confidence: 91%
“…Meanwhile, it could also be contributed by those consumers with both vegetarian–flexitarians and meat‐eaters in their household. In line with our results, a recent study utilizing the Nielsen Consumer Panel data (Cuffey et al, 2021) found that the majority of consumers had not consumed PBMA by 2019, and PBMA spending among the users dropped 75% after the initial purchase, indicating most consumers were probably experimenting with PBMA instead of consuming it regularly. Utilizing national survey data, Taylor et al (2023) also found that consumers do not consume beef and PBMA entirely exclusively of each other.…”
Section: Discussion and Conclusion Remarkssupporting
confidence: 91%
“…We find that only about 30% of the households have more than one purchase for the PBMA, and less than 14% of the households have more than two purchases for the PBMA. The evidence echoes the previous study that 75% of the first‐time consumers of the new generation PBMA stop purchasing these products for the second time (Cuffey et al, 2023). Therefore, it remains challenging for companies of meat alternative burgers to cultivate consumers' product loyalty.…”
Section: Conclusion and Discussionsupporting
confidence: 85%
“…For example, a lot of people assume PBMA competes with beef in the marketplace, but Zhao et al (2023) found that PBMAs are complementary to red meat (beef and pork) and are substitutes for poultry (chicken and turkey) by estimating an almost ideal demand system (AIDS) model with aggregated weekly state-level scanner data. In another study, Cuffey et al (2023) focused on the spending on PBMA and found that household spending on PBMA drops by over 75% after the first purchase of the PBMA. Our paper narrows its focus to a single product (burger) and explores a distinct topic, which differs from previous studies that focus on the aggregated PBMA markets.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In a study conducted in South Africa, Szejda et al (2021) reported that knowing about PBM has a significant positive relationship with PBM purchase intention. A recent study using Nielsen Consumer Panel data (Cuffey et al, 2021) shows that the majority of consumers did not consume PBMs until 2019. It also found that PBM spending among consumers dropped 75% after the first purchase, indicating that most consumers are buying PBM to try it out rather than consuming it on a regular basis.…”
Section: Consumer Opinions About Plant Based Meatmentioning
confidence: 99%